A Jurisprudential Evaluation of Stock-Based Crowdfunding - Mohamadhadi Habibollahi (تحقیقات مالی اسلامی (پیوسته), 2022)
As one of the emerging phenomena, crowdfunding has made a significant contribution to business financing and is surpassing traditional methods such as venture capital and business angels. The stock-based model is considered the most complex type of crowdfunding which has received the attention of various domestic and international platforms, and independent laws have been written for it by governments and policy-making institutions. Therefore, the jurisprudential review of the operational model of active and reliable platforms will be necessary to apply this method of financing inside the country. There are three theories regarding the nature of the shares offered. 1- Shareholders are considered partners of each other; 2- The shareholders have the joint ownership of the company, which is an independent legal entity; 3- We are facing a new phenomenon. The jurisprudential review of the processes was done without presenting an independent opinion and considering all three theories. The relationship between the platform and the business and the relationship between the platform and the investor was designed based on a proxy contract by which it is permissible to terminate the contract and collect fees under the title of attorney's fees by the platform. Also, the possibility of buying and selling shares based on all three theories was considered permissible in compliance with the mentioned terms and conditions.